PEMBUATAN GLASIR KELABU DENGAN MENGGUNAKAN PENCAMPURAN BAHAN PEWARNA BIRU DAN HIJAU - Sundari, Komang Nelly (Badan Pengkajian dan Penerapan Teknologi, 2009)
Have been made three glazes which using 2 (two) raw colorantmaterials, oxide of cobalt and copper oxide. In the glaze, copper oxide from 0,1 % to 0,25 % (weight) while oxide of cobalt equal to 0,10 % (weight). Usage of copper oxide which equal to almost 3 (three) times fold in the reality cannot make dominant green color yielded glazes, even color of greenish blue even also cannot be obtained. Color of the glaze is young blue, indicating that oxide of cobalt more effective as colorant than copper oxide The glaze have maturity which enough at firing temperature 1250oC, having value of L = 68,70, a* from -0,05 to - 0,28 and b* = - 0,40. This value show that the glazes have green color spectrum (marked with value of a* negative) and blue (marked with value of b* negative) and also its young color (marked with value of L* high)